Rheological investigation and optimization of crumb rubber-modified bitumen production conditions in the plant and laboratory - Kok, Baha Vural; Ozdemir, Ahmet Munir (De Gruyter Poland Sp Z O O, 2025)
Among the various bitumen additives, crumb rubber (CR) derived from waste tires stands out due to its economic and environmental advantages. The effectiveness of CR modification is influenced by several factors, including temperature, mixing speed, duration, and particle size. Excessive mixing speed and prolonged mixing in laboratory conditions can lead to the depolymerization of CR, which may adversely affect the elastic properties of the bitumen. In contrast, plant-scale production typically follows a more rapid and simplified process. In this study, bitumen containing 8% CR, modified under plant and laboratory conditions with varying mixing speeds and durations, was rheologically analyzed. Temperature and frequency sweep tests were conducted using a dynamic shear rheometer, and master curves were generated to evaluate the bitumen's viscoelastic behavior through various rheological models. The findings indicate that higher mixing speeds and extended mixing durations in laboratory conditions increase bitumen stiffness; however, excessive mixing leads to depolymerization, thereby reducing its elastic properties. The laboratory-produced CR modification demonstrates significantly superior performance compared to that generated in the plant. Furthermore, response surface methodology optimization analysis results indicate that the ideal conditions for mixing are a speed range of 3,000-4,000 rpm and a duration of 45-60 min.
Keywords: bitumen; rheology; crumb rubber; mixing conditions; master curve